PENINGKATAN KAPASITAS PERANCANGAN STRATEGI PEMASARAN MINUMAN JAHE MERAH INSTAN BAGI UMKM KOMUNITAS ANGGREK KOSAMBI JAKARTA - Setiyaningrum, Ari; Salim, Lina (Fokus ABDIMAS, 2023)
Making instant red ginger drink products become the potential business to develop during the Covid-19 pandemic. Instant red ginger drink is believed can increase the body's immunity against various viruses and diseases so that many people buy and consume it regularly. Komunitas Anggrek Kosambi Jakarta is a community service partner who has started instant red ginger drinks business since the Covid-19 pandemic. But they are facing problems and obstacles regarding instant red ginger drink’s marketing. Partners' lack of knowledge and understanding of product marketing become the reason that instant red ginger drink sells poorly in the market. This community service (PkM) aims to assist partners in overcoming marketing problems through training and mentoring activities to increase partner’s capacity in designing the marketing strategies and the marketing mix of instant red ginger. The approach used in this PkM is community-based research with methods of providing counseling, practice, and mentoring to 40 community members. The pretest and posttest analysis results show that there is an increase in partners' knowledge and understanding in designing marketing strategies and the marketing mix of instant red ginger drink products between before and after participating in training and mentoring activities. The economic impact resulting from this PkM activity is that participants can design marketing strategies and marketing mixes that are suitable for instant red ginger drink so that they can be sold. PkM partners have additional income generated from the sale of instant red ginger and indirectly also improve the family economy.Keywords: covid-19 pandemic, instant red ginger drink, marketing mix, marketing strategy.